Students' Engagement Model in Online Learning Guided by School Counselor during Covid-19 Pandemic - Solihah, Iis; Astuti, Budi; Abubakari, Mussa Saidi (Jurnal Kajian Bimbingan dan Konseling, 2022)
The transformation into online learning during Covid 19 pandemic induces culture shock for students, teachers, and parents. Consequently, students present less participation in online learning. One of the stakeholders capable of improving students’ learning engagement is the school counselor. This study aims to examine secondary school students’ learning involved in the guidance and counseling online program. In this study, we employed a descriptive-quantitative research method, then collected data using a survey method and questionnaire. As many as 293 secondary school students from Java, Indonesia, participated in this study. Further, the obtained data were analyzed using SmartPLS 3. Our analysis results suggested the presence of positive and significant effects of (1) family support on students’ learning engagement; (2) information self-efficacy and communication technology on students’ learning engagement; (3) ICT self-efficacy to students’ interaction with the learning material; (4) school support to students learning engagement; (5) students learning motivation to their learning engagement; (6) students interaction with learning material to their learning engagement; and (7) teachers’ performance to students interaction with the learning material. Meanwhile, teachers’ performance during online learning was observed to have no significant and positive impact on students’ learning engagement.